Analisis penerapan kerangka kerja scrum dan budaya agile pada bisnis Bee Happy Translation - Pratama, Rifky Marda (Maliki Interdisciplinary Journal, 2023)
In the era of VUCA characterized by uncertainty and rapid changes, companies face increasingly complex challenges. Therefore, Agile methods and the Scrum framework emerge as effective solutions. This article analyzes how Bee Happy Translation, a travel agency company, successfully navigated a drastic decline due to the COVID-19 pandemic by adopting Agile culture and the Scrum framework. Through comparative analysis and literature review, the article concludes that the implementation of Scrum and Agile culture provides significant benefits, such as increased productivity, quality, and responsiveness to change. The research findings reveal that the Scrum framework assists the company in swiftly adapting to market changes and uncertainties, while the Agile culture fosters an environment of collaboration, experimentation, and continuous learning. Thus, this article offers insights into how Agile and Scrum approaches can aid companies in confronting the complexity and challenges of a dynamic and uncertain business environment.